Tracing visual knowledge: the presence and value of images for Bedouin history and society in the Negev - Le Febvre, E (2016)
Based on eighteen months fieldwork with Bedouin of the Negev, this thesis explores the varied presence of images as photographs and digital copies for local historicity in order to achieve a greater understanding of representational politics in southern Israel. It emphasizes pictures' ability to transmute, circulate, and acquire value in various social settings in contrast to popular academic treatments, which primarily focus on photographs' iconography and visual history in the Middle East. To do so, the thesis details the biographies of a series of 'significant images' (c. 1906-2010) circulating in this society. It describes their photographic and digital graphic contents as floating referents with the capacity to be coded and recoded by people but also their presence as historical evidence that acquire value in different contexts. The thesis builds on the concept of visual economy as opposed to visual culture in order to landscape images' meanings, material and digital transformations, and their influence for the making of Bedouin history over the last century amid Orientalist, national, and local imaginings. It argues that Bedouin in the Negev possess diverse representational repertoires and utilise a variety of techniques to pursue historical capital. In particular, local representations of the past are selective and instrumental but increasingly reliant on archival mediums such as photographs. Although it may be obvious, anthropologists of the Middle East have yet to adequately account for these occurrences among peripheral peoples and not merely urbanites in the region. Research found that Bedouin spokespersons treat photographs and digital images as evidentiary documentation during self-presentations of historical knowledge in the Negev. As they travel between visual economies, however, images become malleable proof for local history projects alternating between the tribal past, Islamic heritage, and ethnohistory. In conclusion, the thesis develops two theoretical themes in anthropology and visual culture studies of the Middle East: the material and visual efficacy of images for local historicity, and complicating self-representations among Bedouin in the Negev.